The impact of changes in oil prices on monetary and trade policy in Algeria (2000-2017) - Lakhdar Louglaithi; Lahcene Dardouri (Dirassat Journal Economic Issue, 2019)
As Algeria is considered among the rentier states that depend on oil revenues in the implementation of projects and development programs, like other rentier countries of the world, they are affected by fluctuations in oil prices in world markets, and any sudden shift in prices and the subsequent recession and prosperity in economic cycles are situations that policymakers find it difficult to manage effectively. The volatility of prices has exerted effects on the economic policies of the state as a result of monetary and trade policy and fiscal policy negatively affected and positively with the volume of volatile oil revenues, Algeria witnessed the positive and negative fluctuations of oil prices during the period 2000-2017, from the beginning of 2000 to 2014 known In fiscal terms through surpluses resulting from the high oil prices and in the period 2015-2017 has been characterized by a deficit in financial returns, so Algeria sought to take the necessary measures to stabilize its economy in both cases, through its adopted economic policy